Solvent Extraction of Thorium Using 5,11,17,23-Tetra[(2-ethyl acetoethoxyphenyl)(azo)phenyl]calix[4]arene - Quang Hieu Tran; Van Tan Le; Van Cuong Nguyen (Journal of Chemistry)
A rapid, sensitive, and selective method for determination of thorium based on the complex with ortho-ester tetra-azophenylcalix[4]arene (TEAC) was described. In the presence of pH of 4–6, TEAC-Th(IV) complex is extracted from an acidic aqueous solution into chloroform layer. The absorbance intensity of complex was measured by UV-Vis spectrometer at 525 nm and the molar absorptivity was found to be 2.4 × 104. Beer’s law was obeyed in the range of 1.0 to 25 × 10−5 M thorium(IV). The effects of pH, TEAC concentration, and shaking time were also studied. The tolerance limits for several metal ions were calculated. The proposed method was applied to the determination of thorium in synthetic solution and in the monazite sand samples with good results.